A Study of Tuberculous Pleural Effusion in Province 2, Southern Nepal - Kurmi, Roshan; Chaurasiya, Anand; Jha, Sudhakar; Sah, Sanjay Kumar (Med Phoenix, 2023)
Introduction: Tuberculosis (TB) is a major public health problem in developing countries. Tuberculous pleural effusion is the second most common form of extrapulmonary tuberculosis (TB) (after lymphatic involvement) and is the most common cause of pleural effusion in areas where TB is endemic. The aim of this study is to depict the pattern of the Tuberculous Pleural Effusion (TPE) with its clinical presentation and diagnosis along with the different laboratory parameters of the TB patients at a tertiary care center of the Southern Nepal. Materials and Methods: A prospective hospital based cross-sectional study enrolling 107 subjects diagnosed as TBPE presenting to the Department of Internal Medicine, National Medical College was carried out from 15th March, 2023 to 14th October, 2023 (7 months). The different data collected were put in Excel Sheet and analyzed using SPSS version 26. The formal written and verbal consent was taken from the participants and ethical clearance was taken from Institutional Review Committee (IRC), National Medical College, Birgunj (Ref. F-NMC/633/079-080). Results: A total of 107 subjects diagnosed with TBPE showed 67.3 % (n=72) male and 32.7% (n=35) female participants. Majority of the participants (88.8%) presented with fever, and approximately 59% of the participants had chest pain. Almost 65% of them had dyspnea and 77% presented with frank cough. Majority of the participants had right sided effusion. Pleural ,fluid examination showed increased total leukocyte count (mean 3191 cells/cu mm) and with lymphocytic predominance and increased protein content (5.07±0.91 g/dL). Pleural fluid Adenosine Deaminase (ADA)was found to be elevated (86.5±26.4 U/L). Conclusion: The common presentation of the Tuberculous pleural effusion is deranged laboratory parameters of pleural fluid with increased fluid total leukocyte count having lymphocytic predominance and increased protein content along with high ADA levels.